Analisis Terhadap Peran Organisasi IPNU-IPPNU Dalam Perkembangan Sosiologis Di Lingkup Desa Durung Bedug - Mochamad Atok Priwahyudi; Wahyu Eko Pujianto (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
This study aims to analyze the role of the Nahdlatul Ulama Student Association (IPNU) and the Nahdlatul Ulama Putra Putri Association (IPPNU) in the development of socialization in Durung Bedug village. This organization has an important role in shaping social awareness, education, and increasing community involvement in various social and religious activities. The research method used is a type of qualitative approach, descriptive, namely by collecting data and describing it thoroughly according to the problem being solved. This type of research is descriptive, meaning data is presented in the form of text, speech, and observable behavior. Primary data is obtained by researchers through interviews, observations, and document analysis to obtain information about the activities and roles carried out by IPNU and IPPNU in Durung Bedug Village. The analysis was conducted to understand how the role of the organization contributes to increasing social awareness, education, and community participation in social, religious, and cultural life in the village environment. The results of the study show that IPNU and IPPNU have They play a significant role in strengthening social awareness, religious education, and empowering the community in various social and religious activities in Durung Bedug Village. They conduct various programs and activities such as religious guidance, education, training, and capacity building that have a positive impact in advancing the village community socially and spiritually. This research provides a clearer picture of the important role played by IPNU and IPPNU in increasing social awareness, religious education, and community empowerment in Durung Bedug Village. The implications of this research are expected to provide a better understanding of the importance of the role of religious organizations in social development at the village level.